Imagologijos metodas praktikoje - Cidzikaitė, Dalia (Colloquia, 2019)
Imagology Profiles: The Dynamics of National Imagery in Literature, edited by Laura Laurušaitė, Cambridge Scholars Publishing, 2018, 265 pages, ISBN-13: 978-1-5275-1102-6; ISBN-10: 1-5275-1102-2.